Blast Demolition Study of Guyed Masts - Abinet K. Habtemariam; Volkmar Zabel; Marcelo J. Bianco; Carsten Könke (Shock and Vibration)
Demolition of guyed masts is usually carried out by cutting down some of the supporting guy cables using an explosive in such a way that the mast can fall into the desired direction. Without the cable supports, guyed tubular masts are very slender structures which are susceptible to local buckling based on the internal force distribution. If this local buckling occurs at the early stage of the demolition processes, it can cause uncertainty in the failure mechanism. The risk of undesirable demolition outcome due to this uncertainty can be mitigated by using controlled detonation setups. In this paper, a sensitivity analysis is presented using a case study to determine the influence of the explosive detonation time on the collapse development and pattern of the guyed mast. Then, the results of the sensitivity analysis are systematically categorized using cluster analysis to show possible types of collapse regimes which can be used to setup a controlled demolition scheme.